Analisis Laju Perubahan Alih Fungsi Lahan Sawah di Wilayah Kabupaten Pringsewu - Nuraini, Intan; Ridwan, Ridwan; Wisnu, Febryan Kusuma; Asmara, Sandi (abe.fp.unila.ac.id, 2025)
Pringsewu Regency experienced land conversion to increasing land needs. Some of the impacts that can arise as a result of this land conversion include reduced agricultural land, threatened ecosystem balance, agricultural facilities and infrastructure becoming unused, higher urbanization rates, and decreased food production. To study and see how fast the function of rice fields in Pringsewu Regency is changing, a study was carried out regarding the rate of change in the function of rice fields in Pringsewu Regency by utilizing remote sensing techniques with a geographic information system.The results of the research show that there is a trend of decreasing vegetation density levels with the highest decrease in Sukorejo Village (53.37%), a trend of increasing building density levels with the highest increase in Sukorejo Village (45.87%), and a trend of increasing land wetness levels with the highest increase in Bulurejo Village (85.52%) between 2008 - 2022 and obtained a mathematical model Y = 10.7326 - 0.5190 X1 - 0.4007 to predict the rate of change in the conversion of rice fields in the Pringsewu Regency area. Keywords: Geographic Information System, Land conversion, NDBI, NDVI, NDWI.